ANTIPROLIFERATIVE AND APOPTOTIC EFFECTS OF FICUS PSEUDOPALMA BLANCO (MORACEAE) AGAINST HEPATOCARCINOMA (HepG2) - Santiago, Librado A; Mayor, Anna Beatriz R (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objectives.Hepatocellular carcinoma is the third most frequent cause of cancer-related death in the Philippines. The prevalence of this disease continuously pose a great challenge to the medical and health sectors of the country, especially in discovering safe, efficacious and cheap alternative medicines with less or no adverse side effects. Among our endemic medicinal plant species that belong to Moraceae family, Ficus pseudopalma remains understudied. To our knowledge, there are no reports into the molecular mechanisms underlying the growth inhibitory effects of F. pseudopalma against hepatocellular carcinoma. We provided evidence that F. pseudopalma enhances apoptotic cell death of HepG2, specifically targeting DNA damage. Methods. To assess the apoptotic and genotoxic abilities of the plant extract, trypan blue exclusion test, MTT, Comet, TUNEL and Caspase-3 activations assays were performed. Results. Results showed that the crude extract of F. pseudopalma dose-dependently inhibited cell growth of HepG2 recording an IC50 of 353.342µg/mL. Interestingly, all assays indicated apoptotic DNA fragmentation of HepG2 cells at concentrations of 300µg/ml and 1000µg/ml. In particular, changes in morphological features such as aggregation of chromatin, cell shrinkage, and formation of apoptotic bodies were also observed in treated HepG2 cells. Conclusion. The data strongly suggest that F. pseudopalma may be used as an alternative, natural, cheap, readily available, and potent cancer chemoprotective agent by inhibiting cell growth and promoting cell death. The study provides the first molecular evidence on the plant that induces apoptosis for the development of phytotherapeutic regimen for cancer prevention or treatment. Keywords:Ficus pseudopalma, cytotoxicity, apoptosis, Comet assay, TUNEL assay, caspase assay